2011
DOI: 10.1007/s10103-011-0937-7
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric analysis of inflammatory response and necrosis in re-implanted central incisor of rats treated with low-level laser therapy

Abstract: Low-level laser therapy is a tool employed in the management of post-operative inflammation process and in the enhancement of reparative process. The aim of the study was to perform histological evaluation of dental and periodontal ligament of rats central upper-left incisor teeth re-implanted and irradiated with low-level laser (InGaAl, 685 nm, 50 J/cm2) 15, 30, and 60 days after re-implantation. Seventy-two male rats had the central upper left incisor removed and kept for 15 min on dry gauze before replantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 19 publications
2
18
0
4
Order By: Relevance
“…The results of this study showed that in the specimens of G1, the inflammatory process and external inflammatory root resorption varied from moderate (30th day) to intense (60th day). These findings corroborate the results of a previous study which demonstrated that the selection of dry storage promotes cell necrosis of the periodontal ligament and cementum contributing to inflammation and resorption.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study showed that in the specimens of G1, the inflammatory process and external inflammatory root resorption varied from moderate (30th day) to intense (60th day). These findings corroborate the results of a previous study which demonstrated that the selection of dry storage promotes cell necrosis of the periodontal ligament and cementum contributing to inflammation and resorption.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, laser phototherapy has been investigated as a clinical procedure for use after tooth replantation . Previous studies have shown that laser phototherapy increases local microcirculation , fibroblast proliferation , and collagen synthesis in many healing processes.…”
mentioning
confidence: 99%
“…The observed results with the laser group, may be attributed to the modulation of the inflammatory process, which in turn is vital for diminution of the external inflammatory resorption. Vilela et al (39) had shown similar observations, were they found that laser irradiation to the entrance of alveolus and root surface before replantation inhibited the osteoclastic action and enhanced the synthesis of formative cells such as: fibroblasts, cementoblasts, and osteoblasts.…”
Section: Discussionmentioning
confidence: 74%
“…Currently, radiotherapy is one of the selected treatment methods in early diagnosed cases. [8] Ionizing radiation causes chemical damage in tissues, and radiotherapy may cause chemical changes in microcirculation. There is evidence that radiotherapy creates changes in dental pulp.…”
Section: Discussionmentioning
confidence: 99%